Editorial - International Journal of Sustainable Energy Planning and Management Vol 19 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2019)
This editorial introduces the 19th volume of the International Journal of Sustainable Energy Planning and Management. The volume present work on oil and electricity use in Africa, heating and cooling demands for buildings in Algeria, spot and futures markets in the Iberian electricity markets, transportation sector energy scenarios in Indonesia and corporate willingness to adopt renewable energy sources in Nigeria.